Low-frequency interior noise in prop-driven aircrafts: Sources and control methodologies. (July 2017) - Ommi, Fathollah; Azimi, Mohammadreza
Nowadays, noise has turned into one of the most important among the environmental factors on which industry sets down a big part of its efforts and concerns. The recognition of noise as a serious health hazard is a development of modern times. Too much noise obviously impairs our physical and mental existence and therefore it is reasonable to pursue Technology Assessment concerning noisy technologies. The conflicts of interest associated with noise that arise from the operation of airports are well known. Propeller noise is most dominant at low frequencies (below 500 Hz) where traditional passive treatments have only little effect. The many factors contributing to the sound field inside propeller aircraft have led to extensive research directed toward identifying and improving techniques for interior noise reduction.